Characterization of Reactive Astrocytes in the Chronic Phase of the Pilocarpine Model of Epilepsy - Garzillo, Cibele L.; Mello, Luiz E. A. M. (Epilepsia (Copenhagen), 2002)
Purpose: Astrogliosis is a prominent finding in human temporal lobe epilepsy. Work in animal models of temporal lobe epilepsy, however, have mostly concentrated on the acute phases of the studied models or have failed to demonstrate reactive gliosis during the chronic phases of such models. Methods: Here we used the pilocarpine model of chronic seizures and Cajal's gold sublimate technique for the staining reactive astrocytes to study this issue. Results: For half of the animals (nine of 17) subject to pilocarpine‐induced status epilepticus (SE), when assessed 60 days later, variable levels of reactive astrocytes were seen in many thalamic, hippocampal, amygdalar, and neocortical areas. For the remaining half of the animals, however (eight of 17), despite a similar SE induction, as well as for controls, we could not detect stained reactive astrocytes. Conclusions: We hypothesize that these results might underlie possible differences in the frequency of recurrent spontaneous seizures.